Association of Fabry Disease and Psoriasis - therapeutically significant? - Sollfrank, Lukas; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-04-16

Case report: Bullous pemphigoid in HIV-1-positive patients: interplay or coincidence? A case series and review of the literature - Foerster, Yannick; Sollfrank, Lukas; Rechtien, Laura; Harrer, Thomas; Berking, Carola; Sticherling, Michael (Frontiers in Immunology, 2023)
Bullous pemphigoid (BP) is an autoimmune inflammatory skin disease, mostly affecting the elderly population. Therefore, patients often have multiple comorbidities, but there is inconsistent data regarding the relationship between HIV-1 infection and BP, which has been rarely reported in combination. Herein, we describe three patients who presented with BP and concomitant HIV-1 infection that was well controlled with modern combined antiretroviral therapy. All patients received topical and oral corticosteroids. Depending on the individual severity, further add-on therapeutics, such as azathioprine, dapsone, doxycycline and the interleukin 4/13 antibody dupilumab, were added to the therapy regimen. All patients recovered from pruritic skin lesions and blistering. The cases are further discussed in the context of the current study landscape. In conclusion, HIV-1 infection shifts the cytokine profile from T-helper type 1 (TH1) towards T-helper type 2 (TH2), resulting in the excessive secretion of distinct cytokines, such as interleukin 4 (IL-4) and interleukin 10 (IL-10). With IL-4 being a main driver in the pathogenesis of BP, HIV-1-positive patients may benefit greatly from targeting IL-4 with monoclonal antibodies.
CRIS-Team Scopus Importer:2023-07-07
Keywords: aids; bullous pemphigoid; COVID-19; dupilumab; HIV-1; immune reconstitution inflammatory syndrome; iris

Case Report: The many faces of bullous pemphigoid - Rechtien, Laura; Sollfrank, Lukas; Foerster, Yannick; Berking, Carola; Sticherling, Michael (Frontiers in Immunology, 2023)
The pemphigoid group comprises a number of bullous skin diseases with autoantibodies against different constituents of the basement membrane zone that result in subepidermal detachment and clinically characteristic tense blisters, erosions, urticarial erythema, and itching. Apart from the most frequent type of bullous pemphigoid with antibodies against BP180, which is found predominantly in elderly patients, the disease may present at other ages and different pathogenic conditions. Here, four cases are presented of young age (3 months and 25, 34, and 46 years) and in association with vaccination, pregnancy, or metastatic cancer. Though anti-BP180 was found in all cases, a different pathogenic background may be found in any of them, resulting in characteristic clinical manifestation, yet demanding specifically adapted therapeutic approaches.
CRIS-Team Scopus Importer:2023-11-03
Keywords: bullous autoimmune disease; bullous pemphigoid; COVID-19 vaccination; juvenile pemphigoid; pemphigoid gestationis

Impact of off-label use regulations on patient care in dermatology – a prospective study of cost-coverage applications filed by tertiary dermatology clinics throughout Germany - Werner, R. N.; Pennitz, A.; Eisert, L.; Schmidle, P.; Zink, Alexander; Abraham, S.; Schaekel, K.; Wolff; Goebeler, M.; Plange, J.; Sollfrank, Lukas; Zielbauer, S.; et al. (Journal of the European Academy of Dermatology and Venereology, 2022)
Background: In dermatology, a medical speciality with a relatively high number of rare diseases, physicians often have to resort to off-label treatment options. To avoid claims, physicians in Germany can file a cost-coverage request (off-label application, OL-A). Objectives: Our aim was to investigate the extent to which the current regulations affect patient care. Material and methods: Prospective cohort study among tertiary dermatology clinics throughout Germany, consecutively including OL-As (05/2019–09/2020) and assessing the follow-up correspondence. We modelled regressions to assess factors associated with cost-coverage decisions and the time needed by health insurers to process the OL-As. Results: Thirteen clinics provided data on 121 OL-As, two of which applied for on-label treatments. Of the remaining 119 OL-As, 70 (58.8%) were immediately approved and 44 (37.0%) rejected. Including cases with one or more appeals, 87 of 119 OL-As (73.1%) were finally approved and 26 (21.9%) rejected. There was an association of the final approval rate with (1) the class of medication/treatment, with approval rates being significantly lower for JAK inhibitors than for biologics (OR 0.16, 95%-CI: 0.03–0.82); (2) German state, with approval rates being lower in eastern than in western states (OR 0.30, 95%-CI 0.12–0.76); and (3) cost of the intervention (no linear trend). However, none of these predictors was significant in our multiple logistic regression models. The median health insurer's processing time (first response) was 29 days (IQR 22–38). Our analyses showed no evidence of an association with the predictors we assessed. In cases approved, the median time from the decision to file an OL-A to the actual initiation of the treatment was 65.5 days (IQR 51–92). Conclusions: Our study points to substantial delays and inequalities in the provision of timely health care for dermatological patients with rare diseases, often involving treatments for which there is no adequate approved therapy.
CRIS-Team Scopus Importer:2022-07-15

Intravenous Immunoglobulin Therapy for Pyoderma Gangrenosum: A Multicenter Retrospective Analysis in 81 Patients - Ronicke, Moritz; Sollfrank, Lukas; Vitus, Martin V.; Walter, Lukas J.; Krieter, Manuel; Moelleken, Maurice; Dissemond, Joachim; Schultz, Erwin; Lauffer, Felix; von den Driesch, Peter; Erfurt-Berge, Cornelia (American Journal of Clinical Dermatology, 2024)
Background: Pyoderma gangrenosum (PG) is rare neutrophil skin disease causing painful, progressively enlarging ulcers. Among the treatment options, intravenous immunoglobulin (IVIG) is a therapy of first choice for paraneoplastic PG. Otherwise, it is used in therapy-refractory courses. Objective: To assess the efficacy and safety of IVIG therapy in patients with PG. Methods: A retrospective chart review for patients in five dermatologic wound centres in Germany was performed. Results: Overall, 81 patients were included. IVIG was used as adjunct therapy with (methyl-) prednisolone and/or a steroid sparing therapy in 77 (95.1%) cases. Response to treatment (combined complete and partial, defined as tendency to heal and cessation of lesion progression, respectively) was 49.3% 1 month after initiation of IVIG. In total 18.8% had a complete response after 6 months. Statistically significantly higher response rates were observed in patients with diabetes mellitus and thyroid disease [odds ratio (OR) 3.49, confidence interval (CI) 1.13–10.80 and OR 6.64, CI 1.01–43.57, respectively]. Patients with solid malignancy tended to have better response (OR 4.36, CI 0.79–23.91). A higher IVIG dose was also associated with a tendency towards better response rates (OR 2.70, CI 0.84–8.63). In total, 1 (1.2%) severe adverse event (myocardial infarction with consequent death) was observed as well as three moderate adverse events, with two thromboembolic events (2.5%) and one acute kidney injury (1.2%). Other adverse events were mild or unlikely to be associated with IVIG therapy, with 14 events in 10 patients overall (12.3%). Conclusions: This multicentre retrospective study shows the important role of adjunctive IVIG therapy in patients with PG with recalcitrant courses. Identifying subgroups with a higher probability of response could improve future response rates and save patients from ineffective treatment and potential adverse events. Graphical Abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-11-22

Retrospective analysis of autoimmune bullous diseases in Middle Franconia - Sollfrank, Lukas; Schönfelder, Valerie; Sticherling, Michael (Frontiers in Immunology, 2023)
Introduction: Autoimmune bullous diseases (AIBDs) are a group of rare cutaneous disorders affecting cornified skin and mucous membranes. They are characterized by tense or flaccid blistering and erosions due to autoantibodies against desmosomal and hemidesmosomal structural proteins of the skin. This group of disorders can be divided into those of pemphigoid and those of pemphigus diseases. If left untreated, these autoimmune diseases can cause serious or even life-threatening complications such as loss of fluid, superinfections or impaired food intake. Due to modern standardized serological assays, the diagnosis of AIBDs can usually be confirmed in combination with their clinical appearance. Whereas for a long time corticosteroids were the major players in the treatment of these diseases, with the approval of rituximab and other immunosuppressive agents, the therapy has increasingly improved. Methods: In this study, we aimed to investigate epidemiologic and clinical features as well as diagnostics and therapy of bullous autoimmune diseases in Middle Franconia, a governorate within the German federal state of Bavaria. Patients diagnosed or treated because of a AIBDs between 01.04.2013 and 31.03.2019 at the dermatological department of the university hospital Erlangen were included in this retrospective study (n = 242). Patients were either diagnosed for the first time (n=176) or the diagnosis has been confirmed (n=66) at the department. The respective incidence was calculated among the 176 subjects who had been diagnosed at the center in this period. Data was taken from patient records and analyzed with Microsoft® Excel. The evaluation included the diagnoses of pemphigus vulgaris (PV), pemphigus foliaceus (PF), bullous pemphigoid (BP), mucous membrane pemphigoid (MMP), linear IgA dermatosis (LAD), epidermolysis bullosa acquisita (EBA), and dermatitis herpetiformis (DH). Results: This study shows that the incidence of each AIBDs in Middle Franconia is low and comparable (PV, PF, LAD, EBA) or lower (BP, MMP, DH) than in other studies and regions. BP is the most common newly diagnosed AIBD in Middle Franconia. Discussion: Due to the chronic and sometimes severe course of AIBDs, repeated in-house treatments are often necessary. To date, mainly topically and systemically applied corticosteroids in combination with immunomodulators are used as first-line therapy.
CRIS-Team Scopus Importer:2023-11-03
Keywords: autoimmune bullous dermatoses; bullous dermatoses; bullous pemphigod; epidemiology; pemphigoid diseases; pemphigus diseases

Unveiling Metabolic Similarities of Entheses in Patients with Psoriasis and Psoriatic Arthritis Using Noninvasive In Vivo Molecular Imaging: Results From a Cross-sectional Exploratory Study - Fagni, Filippo; Tascilar, Koray; Noversa de Sousa, Rita; Bayat, Sara; Sollfrank, Lukas; Kleyer, Arnd; Sticherling, Michael; Regensburger, Adrian; Knieling, Ferdinand; Neurath, Markus; Schett, Georg; Waldner, Maximilian; et al. (Arthritis and Rheumatology, 2024)
Objective: We assessed and compared molecular tissue changes at the entheses in patients with psoriasis (PsO) and psoriatic arthritis (PsA) and in healthy controls (HCs) in vivo using multispectral optoacoustic tomography (MSOT) and described their relationship with clinical and ultrasound findings of enthesitis. Methods: A cross-sectional study (MSOT and Arthrosonography in PsA) in biologic disease-modifying antirheumatic drug–naïve patients with PsA and PsO and HCs was performed. Participants underwent clinical, ultrasonographic, and MSOT examination of six entheses (lateral humeral epicondyle, distal patellar tendon attachment, and Achilles tendon attachment). MSOT-measured hemoglobin (Hb), oxygen saturation (SO2), collagen, and lipid levels were quantified, and mean differences between groups were calculated using linear mixed effects models. MSOT-measured analytes were compared between entheses with and without clinical and ultrasound anomalies. Results: Ninety participants were included (30 PsO, 30 PsA, and 30 HCs), 540 entheses were clinically assessed, and 540 ultrasound and 830 MSOT scans were obtained. Patients with PsA and PsO showed increased oxygenated Hb (PsA: P = 0.003; PsO: P = 0.054) and SO2 (PsA: P < 0.001; PsO: P = 0.001) levels and decreased collagen signals (PsA: P < 0.001; PsO: P < 0.001) compared with HCs, with more pronounced changes in PsA. Significantly lower collagen levels (P = 0.01) and increased lipids (P = 0.03) were recorded in tender entheses compared with nontender ones. Erosions and enthesophytes on ultrasound were associated with significant differences in SO2 (P = 0.014) and lipid signals (P = 0.020), respectively. Conclusion: Patients with PsA and PsO exhibit an analogous metabolic pattern at the entheses that is exacerbated in the presence of inflammation. These findings support the notion of a psoriatic disease spectrum characterized by common immunometabolic tissue changes.
CRIS-Team Scopus Importer:2024-07-19